2018
DOI: 10.1016/j.orggeochem.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of feather fibers from the Late Cretaceous dinosaur Shuvuuia deserti raises concern about immunohistochemical analyses on fossils

Abstract: Preservation of feather fibers from the Late Cretaceous dinosaur Shuvuuia deserti raises concern about immunohistochemical analyses on fossilsThe MIT Faculty has made this article openly available. Please share how this access benefits you. Your story matters. Citation Saitta, Evan T., et al. "Preservation of feather fibers from the Late Cretaceous dinosaur Shuvuuia deserti raises concern about immunohistochemical analyses on fossils." Organic Geochemistry, 125 (November 2018): 142-151.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 73 publications
4
43
0
Order By: Relevance
“…Despite the many well‐established ways to control for cross reactivity, the issue remains a topic of active debate in the paleomolecular community. For example, a recent study claimed to refute previous immunological data derived from Shuvuuia fibers, a study that was repeated by different investigators, using different antibodies to feather β‐keratin (or corneous β‐protein, CβP), yet which yielded similar results. However, the multiple differences in sample treatment and analytical methodology between the original study and the follow up study make this claim a tenuous one.…”
Section: Protein Studies On Mesozoic Fossilsmentioning
confidence: 95%
“…Despite the many well‐established ways to control for cross reactivity, the issue remains a topic of active debate in the paleomolecular community. For example, a recent study claimed to refute previous immunological data derived from Shuvuuia fibers, a study that was repeated by different investigators, using different antibodies to feather β‐keratin (or corneous β‐protein, CβP), yet which yielded similar results. However, the multiple differences in sample treatment and analytical methodology between the original study and the follow up study make this claim a tenuous one.…”
Section: Protein Studies On Mesozoic Fossilsmentioning
confidence: 95%
“…Nevertheless, the values obtained from both estimations are roughly similar. Therefore, the paleotemperature inscribed in A. vesicularis from the Wido Volcanics would be roughly 340 ± 30 • C. This temperature is sufficient to burn avian feathers into a complete black ash (Saitta et al, 2018, Supplementary Figures S142, S143).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Unfortunately, many of the reports were merely based on the morphology of putative biological structure, thereby another line of evidence should be applied to guarantee the biogenicity of those structures (e.g., Schidlowski, 2001;Gupta et al, 2007;Stein et al, 2019; see also discussion of Schopf et al, 2005). On the other hand, Schweitzer et al (2005) showed the presence of organic materials in the radial section of a titanosaur eggshell using an immunohistochemical approach, which is a superb tool to see a distribution of in situ organic materials and can identify the type of organic material using antigen-antibody reaction (but see also Saitta et al, 2018). Nevertheless, this approach requires rather complicated preparation steps and laboratory resources (see electronic appendix of Schweitzer et al, 2005) that are not easily available to most paleontologists.…”
Section: Introductionmentioning
confidence: 99%
“…The reports of collagen peptides from Mesozoic dinosaur fossils are often viewed as particularly exciting in paleontology as they, if genuine, could dramatically enhance our understanding of the evolutionary biology of extinct organisms through deep time [5]. Despite the increasing number of reports about the preservation of endogenous biocomponents in dinosaur fossils over the last decade, their existence remains controversial due to concerns about exogenous contamination from microbial biofilms [12] and other sources associated with analytical procedures [13][14][15], and to the difficulty in reasonably explaining the mechanisms for their exceptional preservation [5].…”
Section: Discussionmentioning
confidence: 99%